UPAYA GURU BK DALAM MENANGANI PERILAKU AGRESIF SISWA DI SMP NEGERI 12 TARAKAN - Wardani, Usnul; Pribadi, Hendra (Jurnal Bimbingan dan Konseling Borneo, 2019)
Adolescence is a human life span, where adolescents experience development in physical, mental, social, and emotional maturity so that they tend to accentuate negative behavior, one of which is aggressive behavior. To overcome this behavior, the teacher's guidance and counseling efforts are very important. The formulation of the problem in this study is how the teacher's guidance and counseling efforts in dealing with aggressive behavior. The purpose of this study was to find out how the teacher's guidance and counseling efforts in dealing with aggressive behavior of students in SMP Negeri 12 Tarakan. This type of research is descriptive qualitative research. The informants in this study were principals, BK teachers and students. Research instruments are observation, interviews, and documentation. The results showed that (1) the cause of students behaving aggressively is mostly because they have not been able to control emotions, the character of students is hard, and tend to assume that the behavior they do is reasonable and because of lack of supervision, attention and affection from parents so that children tend to feel able to do anything cool and (2) the efforts of BK teachers in dealing with aggressive behavior of students is quite good by providing individual counseling services, group counseling services, conducting home visits, working with parents and homerooms in monitoring student changes. Keywords: Teacher, Guidance and Counseling, Aggressive Behavior.